Respostas

2014-08-07T15:29:56-03:00
Determine a raiz da função 
a- y=5x²+3x-2

5x² + 3x - 2 = 0
a = 5
b = 3
c = - 2
Δ = b² - 4ac
Δ = 3² - 4(5)(-2)
Δ = 9 + 40
Δ = 49------------------------√Δ = 7 --------------porque √49 = 7
se
Δ> 0   duas raízes diferentes
então
(baskara)

x = - b - + √Δ/2a

x' = - 3 - √49 /2(5)
x' = - 3 - 7/10
x' = - 10/10
x' = - 1
e
x" = - 3 + √49/2(5)
x" = - 3 + 7/10
x" = +4/10----------------------------divide ambos por 2 (simplificar)
x" = 2/5


V =  { -1; 2/5}


b-y=3x-6
3x - 6 = 0
3x =+ 6
x = 6/3
x = 2

V = {2}
1 5 1